Aspek Penologis Alasan Peringanan Pidana Bagi Pelaku Tindak Pidana Korupsi - Marasabessy, Syaiful Achmad Zidane; Latupeirissa, Julianus Edwin; Patty, Jetty Martje (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2025)
Introduction: Corruption gets more attention than other crimes because of its huge negative impact. In deciding corruption cases, judges always consider various aspects because they have legal and ethical responsibilities. There is no standard reference regarding the reasons for mitigating or increasing sentences, making it difficult to determine the reasons for light or heavy sentences. Therefore, an in-depth study is needed. Several cases show that penological aspects, such as rehabilitation and reintegration of perpetrators, can be a reason to reduce sentences. Purposes of the Research: This study aims to examine the requirements and role of penological aspects in reducing sentences for corruption perpetrators. Methods of the Research: The legal research used is a normative legal research type which is descriptive and analytical in nature. Results of the Research: The results of the study show that the reasons for reducing sentences for corruption perpetrators include the defendant's awareness and regret, frank confession, never having been convicted, restitution of state losses, family responsibilities, and services to the state or society. However, the use of the penological aspect in the Central Jakarta District Court Decision Number: 29/Pid.Sus-TPK/2021/PN Jkt.Pst is considered odd, especially the reason that the defendant has suffered enough from public insults. This phrase is considered to hurt the sense of justice and should not be used, especially in cases of social assistance corruption when the country is experiencing a non-natural disaster.